ALAT PERMAINAN EDUKASI DALAM MENINGKATKAN MINAT BELAJAR PAI PADA ANAK USIA DINI - Hefniy Hefniy; Mistria Harmonis; Siti Safiah (MANAGERE : Indonesian Journal of Educational Management, 2020)
Educational Game Tool is a media that was developed to assist teachers in enhancing early childhood interest in Islamic Religious Education lessons. This media is a play tool that contains educational elements, so it is suitable with the characteristics of early childhood who tend to like to play rather than learning. The method used in data collection is a library study method. The data obtained is then deductively deducted and then combined to fit the concept of early childhood education. The results of the study showed that the Educational Game Tool media was able to increase children's interest in learning. The types of media Educational Game Equipment used in learning Islamic Religious Education in early childhood, namely; Hijaiyyah Puzzel, Replication of Worship House, Toys Stand for Prayer and Ablution, Hand Puppets, Hijaiyyah Bowling and Tower of Figures